Individual variation is the key to the development of a vaccine against Staphylococcus aureus: a comparative study between mice lineages - dos Santos,D.P. (2018)
Bacterial infections occur worldwide and are a major public health problem. Among pathogens, Staphylococcus aureus is the main causative agent of bacterial diseases in the world. This study aimed to evaluate which components of the immune system could act protectively against a S. aureus infection in intradermally immunized mice. C57BL/6 and A/j mice were immunized intradermally with S. aureus inactivated by heat and then challenged with viable strains in an air pouch model. At 6, 12, and 24 h after the challenge, euthanasia was performed, and the cellular profile of the inflammatory infiltrate, cytokines, and the bacterial load were evaluated in the air pouch lavages. Immunized mice demonstrated that the intradermal immunization with S. aureus promoted protection in C57BL/6 mice by reducing the bacterial, which was correlated with increased serum concentration of IgG antibodies (IgG1 and IgG2a) against S. aureus. The increase in IgG2a antibody levels was correlated with a decrease of bacterial load in intradermally immunized C57BL/6 mice, along with production of IL-17A at the inflammation site, as well as IgG1consumption. Similar results were not found in the A/j lineage. In conclusion, a vaccine against S. aureus should focus more on the individual characteristics of the host because it is a determinant factor for the success of the immunization.